PENDIDIKAN KARAKTER DALAM MENINGKATKAN PERILAKU PESERTA DIDIK KELAS V DI SDN 05 KEPALA HILALANG PADANG PARIAMAN - Hendrizal; Mahesa Putri Kencana; Silvia Oktari; Afdhalul Rafi; Urwatil Wustqa; Romi Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research examines character education efforts to improve behavior of fifth-grade students at SDN 05 Kepala Hilalang Padang Pariaman. Using qualitative descriptive methods, data was collected through interviews, observation, and documentation involving teachers and students. Initial observations revealed serious behavioral problems including school fights, truancy, smoking, bullying, drug use, and extortion among students—behaviors contradicting religious norms and Indonesian law. Findings indicate character education effectively develops positive attitudes like mutual respect and empathy, creating individuals prepared to contribute to peaceful social environments. However, implementation faces challenges including insufficient parental guidance and unsupportive residential environments. These obstacles can be overcome through collaboration between schools, parents, and community awareness. The research demonstrates character education's effectiveness when implemented consistently and comprehensively, requiring systematic planning, execution, and evaluation to build strong student character and improve behavior.